2016
DOI: 10.12775/dem.2016.009
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Analysis between Bitcoin and Selected Global Currencies

Abstract: A b s t r a c t. In this research we have tried to identify the relationship between the exchange rate for bitcoin to the leading currencies such as Dollar, Euro, British Pound and Chinese Yuan and Polish zloty as well. We have applied ARMA and GARCH models to model and to analyze the conditional mean and variance. The appliance of GARCH models have identified some dependency in explanation conditional variance between bitcoin and US Dollar, Euro and Yuan, while ARMA analysis have shown no relations between bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Both practitioners and theorists of financial markets have problems with the clear classification of cryptocurrencies and with indicating that universal mechanisms influence and explain the behavior of cryptocurrencies in the financial space. For further information on bitcoin and other cryptocurrencies, please refer to Liu et al (2015), Szetela et al (2016Szetela et al ( , 2020, Urquhart (2017), Corbet et al (2018).…”
mentioning
confidence: 99%
“…Both practitioners and theorists of financial markets have problems with the clear classification of cryptocurrencies and with indicating that universal mechanisms influence and explain the behavior of cryptocurrencies in the financial space. For further information on bitcoin and other cryptocurrencies, please refer to Liu et al (2015), Szetela et al (2016Szetela et al ( , 2020, Urquhart (2017), Corbet et al (2018).…”
mentioning
confidence: 99%
“…Atik et al (2015) investigated the impact of bitcoin on foreign exchange rates and determined that there is a one-way causality from Japanese Yen to Euro, and these two currencies are affected from each other. Szetela, Mentel and Gedek (2016) in their work, according to the results of the ARMA process, Bitcoin acts independently from other currencies in the analysis. The conditional variance of Bitcoin modeled with the GARCH process is affected by the Euro, Dollar and Yuan returns.…”
Section: Literaturementioning
confidence: 99%
“…The process of discovery to find out significant patterns, critical figures, or important connections to identify significant points about the relationship of these two concepts has a key role for the financial analysis in this field. Szetela et al (2016) identified the correlation among various currencies (i.e., Euro, Chinese Yuan, US Dollar, and the British pound). Similarly, Özdemir et al (2018) evaluated the price changes of cryptocurrencies and real money in the context of historical value changes in their analysis.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In this research, the correlations of cryptocurrencies with financial assets or commodities other than fiat currencies typically contain gold, silver, stocks, and oil crude market (Cryptocurrency Market Capitalizations; Gajardo et al, 2018;Szetela et al, 2016). Dyhrberg (2016) emphasized the comparison of Bitcoin and gold in terms of hedging capabilities, where Klein et al (2018) analyzed conditional variance properties of Bitcoin and gold to reflect linkages and distinctive properties of these assets.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%